2019
DOI: 10.3390/ma12162507
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Precipitates by Simple Cold Deformations to Strengthen Mg Alloys: A Review

Abstract: Regulating precipitates is still an important issue in the development of high-strength Mg alloys, due to it determining the precipitation hardening effect. Cold deformation, as a simple and low-cost method, can remarkably influence the precipitate features. It is found that pre-cold deformation before aging can be utilized to enhance the precipitation hardening effect of Mg alloys. Moreover, post-deformation after aging could be an effective method to regulate precipitation orientation. In this review, recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Alloying and grain refinement are the main ways to improve the mechanical properties of Mg alloys [ 11 ]. Previous studies have shown that the addition of rare earth (RE) elements can significantly enhance the mechanical properties of Mg alloys [ 12 , 13 ]. However, in general, RE elements are not only dense but also expensive, which is not suitable for large-scale commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Alloying and grain refinement are the main ways to improve the mechanical properties of Mg alloys [ 11 ]. Previous studies have shown that the addition of rare earth (RE) elements can significantly enhance the mechanical properties of Mg alloys [ 12 , 13 ]. However, in general, RE elements are not only dense but also expensive, which is not suitable for large-scale commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Mg and its alloys are currently receiving widespread attention, especially in the automobile industry, due to the low density and high specific strength [1,2]. However, the low stretch formability at room temperature largely limits the widespread application of Mg alloy sheets [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium alloys are considered as promising structural materials in the automotive and aerospace industry because of their low density, high stiffness, and easy recycling [1,2,3]. But, at present, magnesium alloys are not widely used and cannot completely replace steel and aluminum alloys.…”
Section: Introductionmentioning
confidence: 99%